Multi-Frequency Contrast Source Inversion for Reflection Seismic Data (Communications in Computational Physics, 2020)
In the contrast source inversion (CSI) method, the contrast sources (equivalent scattering sources) and the contrast (parameter perturbation) are iteratively reconstructed by an alternating optimization scheme. Traditionally integral equation CSImethod is formulated for transmission tomography using analytic Green's functionin homogeneous background. To extend the method to the case of reflection seismology, in this paper, we use WKBJ method to compute the Green's function of depthdependent background media and the solving method of equations to initialize thecontrast source of different frequencies, resulting in an efficient method to invert multi-frequency reflection seismic data – multi-frequency contrast source inversion method(MFCSI). Numerical results for the Marmousi model show that MFCSI method canobtain good results even when low frequency data are missing, in which case the conventional FWI fails.
Keywords: Contrast source inversion; full waveform inversion; frequency domain inversion; integral equation CSI.